PENGARUH AKSESIBILITAS DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN DENGAN JAMINAN RASA AMAN SEBAGAI VARIABEL INTERVENING - Rahayu, Tri Puspito; Subagyo, Subagyo; Widodo, Moch. Wahyu (Universitas Nusantara PGRI Kediri, 2022)
This study aims to determine the effect of accessibility and trust on purchasing decisions with a sense of security as an intervening variable at the Nganjuk Cosmetic Skincare Agent. The research approach used is quantitative and is a type of causality research. The population in this study were consumers of skincare products from the Nganjuk Cosmetics Agent whose number was unknown. The sample was determined by 40 respondents who were taken using a non-probability sampling technique. The data collection method used a questionnaire which was then analyzed using path analysis which was then processed using the SPSS 23 program and through the Sobel test. The research findings reveal that security guarantees can mediate accessibility and trust in purchasing decisions of skincare consumers at the Nganjuk Cosmetics Agent. For that Nganjuk Cosmetics Agent needs to further improve in providing service satisfaction to consumers so that it can create consumer interest to repurchase.